A study of speaking in tongues in Acts and 1 Corinthians and its use and abuse in some selected contemporary churches in Nigeria - Oyebowale Oyetade, Michael (Stellenbosch Theological Journal, 2020)
There are much confusion and controversy in our churches today about the phenomenon known as speaking in tongues. Some claim that the gift of speaking in tongues continues in our time as the Holy Spirit miraculously moves persons to speak in a language they had never learned. Other believers are convinced that the Scriptures leave no room for the continuation of that special gift beyond the founding era of the Apostolic church. To worsen it all pagans abound in such ecstatic utterances and are convinced they are from God. The objective of this paper is to investigate both the use and abuse of speaking in tongues. Historical and exegetical methods were used. Data were gathered through primary and secondary sources. The paper found out that speaking in tongues was miraculously used by God at Pentecost and in the earliest churches in the apostolic era. But there were distinguishing features that marked it out from the psychological phenomenon found among pagans. In our contemporary church in Nigeria, the only way to test the source is by comparison with what God explains in his word about the purpose and occasion for the legitimate manifestation.